Frankenstein in fact and fiction: Lecture at Bard College, November 19, 2024 - Robert Jacob Alexander Skidelsky (Levy Economics Institute of Bard College, 2024)
As we all know, Frankenstein was the scientist in Mary Shelley's 1818 novel of the same name, who invented a human machine-intended to be a benefactor, but which turned out to be a monster. There is a critical question I wish to address this evening: Can we avoid our technology destroying us? This is the most important thread that runs through my book, Mindless (2024), recently published in the United States. The book discusses the impact of machines on jobs, on freedom, and on our survival as a species. The question that dominates all three concerns the impact of machines on our humanness. Today we ponder whether there is still time to control the Machine before it controls us. I will talk about three Frankensteins who each set out to create gods and, in turn, created monsters.
Keywords: 330